Kampanye Penanganan Sampah dan Pengadaan Keranjang Sampah Pada Pedagang Kaki Lima Di Pantai Talise - Mustafa, Mustafa; Maryam, Maryam; A Bungawati (Joong-Ki : Jurnal Pengabdian Masyarakat, 2023)
Garbage is a common problem faced by a community or a city. Because almost all activities or activities carried out by the community produce waste. One of the waste problems in Palu City is Talise beach. The lack of trash cans and the lack of awareness and knowledge of traders about waste and its effects resulted in the scattering of garbage on Talise beach. The purpose of this community service is to provide campaigns to traders and provide trash bins. The service method used is surveys and conducting campaigns or counseling. The results of the community service show that there has been a change in traders in disposing of trash and the enthusiasm of the traders in utilizing the distributed trash cans